David Nash - Nash, David (Thames & Hudson, 2007)
"David Nash (b. 1945) is an artist internationally renowned for working with wood to form large, dramatic and tactile sculptures. He has created a significant and varied body of work in which the relationship between man and nature is a central theme. His artistic ethos has always been one of direct, physical involvement with his chosen material - wood - and the landscape. This book is the first major monograph on this popular and acclaimed artist, whose recent shows have enjoyed tremendous success." - publishers description.
Keywords: Nash, David / 1945-; Nash, David <1945->